Autologous chondrocyte transplantation in the repair of full-thickness focal cartilage damage in rabbits - Kamarul, Tunku; Selvaratnam, L.; Masjuddin, T.; Ab-Rahim, S.; Ng, C.; Chan, K.Y.; Ahmad, T.S.T. (SAGE Publications (UK and US), 2008)
PURPOSE:To compare the efficacy of autologous chondrocyte transplantation (ACT) versus non-operative measures for cartilage repair in rabbits. METHODS:Nine New Zealand white rabbits were used. Identical focal defects were created in the articular cartilage of both knees. One month later, the right knee was repaired via ACT, while the left knee was left untreated (control group). The quality of cartilage tissues in both knees was compared 3 months later, according to the quantitative analysis of glycosaminoglycan (GAG) in the cartilage and macroscopic examination of histology using the Brittberg/International Cartilage Research Society (ICRS) score. RESULTS:Microscopic examination showed enhanced regeneration following ACT repair. Quantification analysis revealed significantly higher cellular expression of GAG in the ACT-treated knees (1.12 vs 0.81 microgram GAGs/mg protein, p=0.008). The mean Brittberg/ICRS score was significantly higher in the treated knees (6.00 vs 1.89, p=0.007). CONCLUSION: ACT is superior to non-operative measures for repairing focal cartilage defects, as determined by favourable histological and immunohistological outcomes at the cellular level.